SYSTEMATIC LITERATURE REVIEW: PENGARUH TEKANAN WAKTU DAN KOMPLEKSITAS AUDIT TERHADAP PERILAKU DISFUNGSIONAL AUDITOR - Fathimah Aulia Hafshah; Muhammad Munadil Haq; Muh. Nursalim Abduh; Suci Ramadani; Wahyuni Bt. Kadir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Auditing plays a crucial role in ensuring the reliability of financial information; however, auditors often face pressures that trigger dysfunctional behaviors, such as neglecting audit procedures, premature sign-off, or reducing the quality of audit evidence. This study aims to analyze the influence of time pressure and audit task complexity on auditors’ dysfunctional behavior. The method used is a Systematic Literature Review (SLR), analyzing 10 relevant articles published between 2020 and 2025. The findings indicate that both time pressure and audit complexity consistently increase the risk of dysfunctional behavior. The interaction of these factors creates a professional dilemma, further reinforced by psychological and organizational conditions such as role conflict and locus of control. These findings provide practical implications for public accounting firms in managing auditors’ workload, setting realistic time budgets, and enhancing audit quality through training and a work culture that supports professional integrity.